Implementation of the Kurikulum Merdeka in Mathematics Learning at Elementary Schools - Wahyono, Wahyono; Wahyudi, Achmad Basari Eko; Salimi, Moh; Hidayah, Ratna; Fajari, Laksmi Evasufi Widi; Wijaya, Tommy Tanu (Jurnal Pendidikan Progresif, 2024)
Abstract: Implementation of the Kurikulum Merdeka in Mathematics Learning at Elementary Schools. Objectives: This study aims to examine the implementation of the Kurikulum Merdeka in enhancing the potential of mathematics learning in elementary schools in Kebumen Regency. Methods: The research was conducted using a qualitative approach with phenomenological methods. Participants of this study were teachers and principals in 5 elementary schools recruited through purposive sampling techniques. Data were garnered through observation, interviews, and documentary studies. Interviews were conducted with educators and school principals. The data analysis technique consists of data collection, data reduction, data presentation, and drawing conclusions. Findings: The results of the study indicate that: (1) the planning of mathematics learning in Kurikulum Merdeka is prepared by teachers through informal learning and collaboration with peers; (2) the implementation of mathematics learning in Kurikulum Merdeka is still in the stage of adapting various teaching experiences of teachers; (3) the evaluation of mathematics learning in Kurikulum Merdeka already uses diverse evaluation tools and types of questions. Conclusion: This study concludes that the implementation of the mathematics learning involves planning with informal learning methods, adapting the implementation of learning, and various evaluation methods. Keywords: kurikulum merdeka; mathematics; elementary school; qualitative phenomenology.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202440